2022
DOI: 10.3390/molecules27175652
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Absorptive Microsampling (VAMS) for Targeted LC-MS/MS Determination of Tryptophan-Related Biomarkers

Abstract: L-Tryptophan (TRP) metabolites and related biomarkers play crucial roles in physiological functions, and their imbalances are implicated in central nervous system pathologies and neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS), Alzheimer’s disease, Parkinson’s disease, schizophrenia and depression. The measurement of TRP metabolites and related biomarkers possesses great potential to elucidate the disease mechanisms, aid preclinical drug development, highlight potential therapeutic targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Microsampling technologies have been evaluated in biomarker research studies for the diagnosis and prognosis of various conditions and the prediction and monitoring of response to an intervention 24,41,42,132–144 . Omics‐based approaches, such as metabolomics and proteomics, are increasingly employed for the generation of large amounts of data to facilitate the rapid discovery of biomarkers.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microsampling technologies have been evaluated in biomarker research studies for the diagnosis and prognosis of various conditions and the prediction and monitoring of response to an intervention 24,41,42,132–144 . Omics‐based approaches, such as metabolomics and proteomics, are increasingly employed for the generation of large amounts of data to facilitate the rapid discovery of biomarkers.…”
Section: Applicationsmentioning
confidence: 99%
“…Based on a Net Promotor Score, upper arm sampling was found to be preferred over finger prick sampling by patients 24 . Other studies that have implemented the VAMS technology include research for (i) the human biomonitoring of mercury concentrations for exposure assessment, 41,145 (ii) the determination of tryptophan‐related biomarkers for understanding pathologies of neurodegenerative diseases such as Alzheimer's or Parkinson's disease 138 and (iii) the measurement of endocrine and bone biomarkers 139 . VAMS technology was also capable of detecting carcinogens, such as acrylamide and aflatoxin B 1 140,141 …”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, VAMS facilitates participants’ self-collection of blood, hence supporting remote health monitoring and avoiding unnecessary extra hospital visits [ 9 ], which can be a burden, especially for the elderly. Moreover, it minimizes volume collection and does not, generally, require refrigerated transport and storage conditions [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the tryptophan metabolism pathways, since indole metabolites on the indole metabolism pathway can only be produced via gut microbiota and influence the immune system and CNS in the human body as ligands for the aryl hydrocarbon receptor (AhR), indole metabolites have been speculated to play a key role in the gut-brain axis [14]. For this reason, to find potential biomarkers for several diseases, analytical approaches to detect gut microbial metabolites, including tryptophan metabolites, have been developed [15][16][17]. Furthermore, since it was reported that indole-3-propionic acid and other microbial metabolites were changed in the plasma of PD patients [18], the interest in changes in indole metabolites in PD patients has been continuously increasing.…”
Section: Introductionmentioning
confidence: 99%